1999
DOI: 10.1021/bi990174x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Macrocyclic Peptidomimetic Inhibitors by HIV-1 Protease,

Abstract: High-resolution crystal structures are described for seven macrocycles complexed with HIV-1 protease (HIVPR). The macrocycles possess two amides and an aromatic group within 15-17 membered rings designed to replace N- or C-terminal tripeptides from peptidic inhibitors of HIVPR. Appended to each macrocycle is a transition state isostere and either an acyclic peptide, nonpeptide, or another macrocycle. These cyclic analogues are potent inhibitors of HIVPR, and the crystal structures show them to be structural mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 35 publications
4
83
0
1
Order By: Relevance
“…This is consistent with results obtained from NMR studies (12,16), and therefore a discrete structural intermediate in substrate recognition by HIV-1 protease has been trapped. Both of the flaps in the dimer could potentially assume an intermediate geometry within this crystal form; however, only the flap interacting with the P4-P1 side of the substrate adopts a closed conformation, implying that the P3-P1 region of the substrate may be crucial for specificity (1,27,42). The crystal structure of HIV-1 protease product complex retains only the P5-P1 side (Ac-Ser-Leu-Asn-Phe/) of the substrate Ac-SerLeu-Asn-Phe*Phe-Leu-Glu-Lys (PDB code 1YTH) (43).…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with results obtained from NMR studies (12,16), and therefore a discrete structural intermediate in substrate recognition by HIV-1 protease has been trapped. Both of the flaps in the dimer could potentially assume an intermediate geometry within this crystal form; however, only the flap interacting with the P4-P1 side of the substrate adopts a closed conformation, implying that the P3-P1 region of the substrate may be crucial for specificity (1,27,42). The crystal structure of HIV-1 protease product complex retains only the P5-P1 side (Ac-Ser-Leu-Asn-Phe/) of the substrate Ac-SerLeu-Asn-Phe*Phe-Leu-Glu-Lys (PDB code 1YTH) (43).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the positions corresponding to the P3-P1Ј sites of the substrates may be used to model inhibitors instead of using the positions of P2-P2Ј. A recent study has revealed that inhibitors with a macrocyclic group connecting the P3 and P1 residues are likely to be more efficient (35).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of macrocyclic peptidomimetics, tighter packing of the active site loops of HIV Pr has been correlated with increased binding affinity (41). Clustering of the protein on the basis of ADP interaction profiles indicates that the flaps of monomer A and B and the P1′ binding loop exhibit similar anisotropic motions possibly due to interactions among the flaps.…”
Section: Discussionmentioning
confidence: 99%